Populus SVL Acts in Leaves to Modulate the Timing of Growth Cessation and Bud Set - André, Domenique; Zambrano, José Alfredo; Zhang, Bo; Lee, Keh Chien; Rühl, Mark; Marcon, Alice; Nilsson, Ove (Frontiers in Plant Science, 2022)
SHORT VEGETATIVE PHASE (SVP) is an important regulator of FLOWERING LOCUS T (FT) in the thermosensory pathway of Arabidopsis. It is a negative regulator of flowering and represses FT transcription. In poplar trees, FT2 is central for the photoperiodic control of growth cessation, which also requires the decrease of bioactive gibberellins (GAs). In angiosperm trees, genes similar to SVP, sometimes named DORMANCY-ASSOCIATED MADS-BOX (DAM) genes, control temperature-mediated bud dormancy. Here we show that SVL, an SVP ortholog in aspen trees, besides its role in controlling dormancy through its expression in buds, is also contributing to the regulation of short day induced growth cessation and bud set through its expression in leaves. SVL is upregulated during short days in leaves and binds to the FT2 promoter to repress its transcription. It furthermore decreases the amount of active GAs, whose downregulation is essential for growth cessation, by repressing the transcription of GA20 oxidase. Finally, the SVL protein is more stable in colder temperatures, thus integrating the temperature signal into the response. We conclude that the molecular function of SVL in the photoperiodic pathway has been conserved between Arabidopsis and poplar trees, albeit the physiological process it controls has changed. SVL is thus both involved in regulating the photoperiod response in leaves, modulating the timing of growth cessation and bud set, and in the subsequent temperature regulation of dormancy in the buds.